2022
DOI: 10.3390/chemistry4030047
|View full text |Cite
|
Sign up to set email alerts
|

Piperine Derivatives Enhance Fusion and Axonal Transport of Mitochondria by Activating Mitofusins

Abstract: Piperine (1-piperoylpiperidine) is the major pungent component of black pepper (Piper nigrum) and exhibits a spectrum of pharmacological activities. The molecular bases for many of piperine’s biological effects are incompletely defined. We noted that the chemical structure of piperine generally conforms to a pharmacophore model for small bioactive molecules that activate mitofusin (MFN)-mediated mitochondrial fusion. Piperine, but not its isomer chavicine, stimulated mitochondrial fusion in MFN-deficient cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Mitofusin activators were only recently described and, to our knowledge, are the only small molecules that directly enhance mitochondrial fusion and transport. Multiple mitofusin activator chemical backbones have been described ( Rocha et al, 2018 ; Dang et al, 2021 ; Zhang et al, 2022 ), each of which chemically mimic MP1, a MFN2-derived peptide that competitively inhibits peptide-peptide interactions that determine MFN1 and MFN2 folded versus unfolded tertiary structure ( Franco et al, 2016 ; Rocha et al, 2018 ). Competing peptide MP1 and small molecules that mimic MP1 critical peptide side chains ( Rocha et al, 2018 ) promote MFN extended or unfolded conformations, thereby evoking mitochondrial fusion and motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitofusin activators were only recently described and, to our knowledge, are the only small molecules that directly enhance mitochondrial fusion and transport. Multiple mitofusin activator chemical backbones have been described ( Rocha et al, 2018 ; Dang et al, 2021 ; Zhang et al, 2022 ), each of which chemically mimic MP1, a MFN2-derived peptide that competitively inhibits peptide-peptide interactions that determine MFN1 and MFN2 folded versus unfolded tertiary structure ( Franco et al, 2016 ; Rocha et al, 2018 ). Competing peptide MP1 and small molecules that mimic MP1 critical peptide side chains ( Rocha et al, 2018 ) promote MFN extended or unfolded conformations, thereby evoking mitochondrial fusion and motility.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of small molecule mitofusin activators made it possible to investigate mitofusin functioning without experimentally perturbing Mfn1 or Mfn2 levels. To date, three chemical classes of mitofusin activators have been described: triazolureas ( Rocha et al, 2018 ; Zacharioudakis et al, 2022 ), phenylhexanamides ( Dang et al, 2020, 2021 ), and derivatives of the natural compound piperine ( Zhang et al, 2022 ). All of these small molecule mitofusin activators chemically mimic amino acid side chains that determine mitofusin protein conformation.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, since fusion emerges to play a potentially crucial role in male fertility and hormonal therapy effectiveness, this process may represent a prospective candidate for combined therapy. Some drugs that increase mRNA expression or activation of MFN1/MFN2 have been described in in vivo models, thus opening the way to their application for other diseases [ 153 , 154 , 155 ]. Nevertheless, it is important to consider that this therapy should be tissue-specific to avoid a general alteration in mitochondrial homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Life-long Mfn2 overexpression (i.e., from before birth and therefore prior to disease) delayed ALS onset and prolonged the survival of SOD1 G93A mice. A pathophysiological role proposed for Mfn2-mediated calpastatin transport on mitochondria is somewhat controversial [ 87 ] and would be difficult to distinguish from the general improvement in mitochondrial motility, transport and delivery to distal neuronal termini provoked by mitofusin activity [ 87 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. Nevertheless, these studies confirmed previous findings that neuronal Mfn2 ablation adversely impacts neuronal function in vivo [ 106 , 107 , 108 ], while demonstrating that enhanced mitochondrial fusion can delay phenotype progression in this model.…”
Section: Mitochondrial Dysdynamics As a Therapeutic Focus In Neurodeg...mentioning
confidence: 99%
“…Thus, medical interventions for chronic clinical conditions overwhelmingly favor the use of small molecule pharmaceuticals. It is therefore fortunate that multiple small molecules have recently been described which may favorably impact the disequilibrium between mitochondrial fusion and fission in neurodegeneration [ 87 , 99 , 100 , 102 , 103 , 109 ].…”
Section: Mitochondrial Dysdynamics As a Therapeutic Focus In Neurodeg...mentioning
confidence: 99%